Japanese technology transfer (JTT) to Malaysia : Re-assessment in globalization induced changing environment / Zainal Abidin Sanusi and Hideo Kobayashi - Sanusi, Zainal Abidin; Kobayashi, Hideo (Universiti Teknologi MARA Cawangan Pahang, 2004)
There have been mixed opinions and skepticisms on the contribution of Japanese technology transfer to Malaysian indigenous technology development. This paper seeks to review the issue and explore reasons for the differences and disagreements towards refining findings on the issue. Analysis is carried out within the perspective of changing context of technology transfers as a result of globalization process. Such changes suggest necessary revision of framework and approach in technology transfer analysis. Japanese technology transfer to Malaysia provides an excellent case study of how these changes took place and how the issues of approaches and measurements in technology transfer are proven to be very critical in assessing any technology transfer process.